Assessment tuberculin skin test specificity in water buffalo using five different antigens - Alessandra Martucciello; Francesco Napolitano; Piera Mazzone; Francesco Grandoni; Maria Beatrice Boniotti; Monica Cagiola; Gabriele Di Vuolo; Felice Gerardo Giglio; Francesco Grippa; Giorgio Galiero; Federica Signorelli; Esterina De Carlo (Revista Científica)
Tuberculosis (TB) control involves “test and cull strategies”. The primary diagnostic test is the tuberculin skin test (TST) which requires intradermal inoculation with specific My cobacterium bovis antigens, bovine tuberculin (PPDB) in the single intradermal reaction test (SIT) and avian tuberculin (PPDA) in the comparative intradermal reaction test (SICT). Using other antigens susch as 6 kDa early secretory antigenic target (ESAT-6), 10 kDa culture filtrate protein (CFP-10) and Early Secretory Proteins (ESP) could increase test specificity. Therefore, this study aims to evaluate the specificity of TST using five different antigens. A total of 100 buffaloes from 3 TB free Italian herds were enrolled. Five intradermal injection sites on the animal’s shoulder (three on the right and two on the left side) were used on each animal, with a volume of 0.1 mL for all antigens (ESAT-6 and CFP-10 at 20 μg/mL, ESP at 100 μg/mL, PPDA and PPDB at 100 μg/mL), and PBS as negative control. Skin reactions were measured using calipers. Results were expressed in millimeters as the difference between the two measurements, i.e., before and 72h after the inoculation of tuberculin. The reaction was considered positive if skin thickness increased by ≥ 4mm, doubtful if >2 and <4mm, and negative if ≤ 2 mm. All 100 buffaloes were also submitted to the gamma-interferon (IFN-γ) test to confirm TB negativity. Of the 100 negative subjects, 31 gave doubtful SIT results to PPDB while the number of doubtful subjects decreased to 11 with the SICT. The number of doubtful results with ESP stimulation was 26 and with the ESAT-6 and CFP-10 protein cocktail, it was 21. If we introduce the responses to stimulation with ESP and ESAT-6 and CFP-10 protein cocktail combined with the interpretation of SICT, the 11 doubtful results would be reduced to 5 and 4, respectively. The doubtful outcomes of SIT and SICT found in negative animals with PPDB and PPDA stimulation, could be due to non-specific responses. In buffalo, this non-specificity could be due to atypical mycobacterial infections as well as to the peculiarities of buffalo skin structure compared to bovine skin (e.g., dermis thickness). Regarding ESAT-6 and CFP-10 protein cocktail and ESP, they induced fewer non-specific reactions, and thus, they could be used in SICT in association with traditional PPDs. Due to the IFN-γ test, we excluded the presence of anergic subjects, since all 100 subjects reacted to stimulus with the mitogen. Furthermore, the IFN-γ test in the same animals gave negative results according to the interpretation criteria of the official EU IFN-γ test, even if with slight non-specific reactions, but excluding false-positive results.